Evaluasi Program Pendidikan Pada Anak Usia Dini Menggunakan Model CIPP - Nelly Agustina; Rizky Hermalia; Zuraidah Hanum Nasution; Nayla Cantika Nur Azizah (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Program evaluation is an essential component of early childhood education (ECE) to ensure the achievement of learning objectives and improve the quality of educational services. One of the most widely used evaluation approaches is the Context, Input, Process, Product (CIPP) model because it provides a comprehensive framework for assessing program planning, implementation, and outcomes. This study aims to analyze the implementation of the CIPP model in evaluating early childhood education programs and to identify its benefits and challenges based on previous research findings. This study employed a qualitative approach using a literature review method. Data were collected from national and international journal articles, academic books, conference proceedings, and policy documents related to early childhood education program evaluation and the CIPP model. Data were analyzed using content analysis through data reduction, categorization, interpretation, and synthesis of previous research findings. The results indicate that the CIPP model is a systematic and comprehensive evaluation approach because it assesses program needs (context), resource readiness (input), implementation processes (process), and program outcomes (product). The application of the CIPP model enables early childhood education institutions to identify program strengths, weaknesses, and areas for continuous improvement, thereby enhancing the quality of educational services. Therefore, the CIPP model is considered an appropriate evaluation framework for supporting continuous quality improvement in early childhood education programs